Delayed Graft Function in Kidney Transplantation: Risk Factors and Impact on Early Graft Function. (June 2016) - Tugmen, Cem; SERT, Ismail; Kebabcı, Eyup; Murat Dogan, Sait; Tanrısev, Mehmet; Alparslan, Caner; Kılıcaslan Ayna, Tulay; Olmez, Mustafa; Karaca, Cezmi
Context: Although kidney transplantations are routinely performed at many centers in Turkey, the incidence and risk factors associated with delayed graft function (DGF) here have not yet been well defined. Objective: The aim of this study is to evaluate the incidence and risk factors of DGF and its impact on early graft function. Design: The medical charts of 154 adult patients who underwent deceased donor kidney transplantation between 2000 and 2014 in a single center were reviewed retrospectively. Setting: Delayed graft function-related risk factors for donors, recipients, and the transplant surgery itself were analyzed, and their relation with graft function was evaluated. Main Outcomes Measures: The median recipient age was 39 years. The median cold ischemia time (CIT) was 840 minutes (14 hours). The incidence of DGF and acute rejection were 57.8% and 8.4%, respectively. Higher serum creatinine levels at 3, 6, and 12 months were observed in patients with DGF compared to other patients without DGF ( P < .05). Patients with DGF had poor graft function (glomerular filtration rate ≤ 50) at 3 and 6 months ( P < .05), but these correlations were not seen at 12 months ( P = not significant). Results: This study showed that DGF was a common and serious problem associated with poor graft functions at 3, 6, and 12 months after transplantation. Extra effort to shorten CIT as an independent risk factor for DGF could have protective effect on graft functions.